"You Tweet Like a Girl!": How Female Candidates Campaign on Twitter. (March 2016) - Evans, Heather K.; Clark, Jennifer Hayes
We investigate the Twitter activity of all congressional candidates leading up to the 2012 U.S. House elections to assess whether there are significant differences in the tone and content of the tweets from male and female candidates. We argue that the electoral environment will have a significant effect over whether candidates engage in negative tweeting, address political issues, and discuss so-called "women's issues" on Twitter. We find that gender has both a direct and contextual effect on candidates' communication style on Twitter. Female candidates tweet significantly more "attack-style" messages than their male counterparts, discuss policy issues at a significantly higher rate, and women representatives focus more on "women's issues." We also find strong contextual effects in races with more female candidates: There is significantly more tweeting about political issues as well as significantly more negative attack-style tweets. However, with more female candidates, the number of tweets about "women's issues" declines.